Ответы и объяснения

  • 2407Alexa
  • почетный грамотей
2013-12-17T20:34:51+04:00
1)D=(-37)^2-4*1*27=1369-108=1261
x1=(-(-37)+35,5)/2*1=72,5/2
x1=36,25
x2=(-(-37)-35,5)/2=1,5/2
x2=0,75
x1+x2=36,25+0,75=37
x2=36,25*0,75=27,19
2) x(x-210)=0
x1=0
x2=210
x1+x2=0+210=210
x1*x2=0*210=0
3)y(1-y)=0
y1=0
y2=1
y1+y2=0+1=1
y1*y2=0*1=0
4)D=41^2-4*1*(-371)=1681+1484=3165
x1=(-41+56,26)/2=15,26/2
x1=7,63
x2=(-41-56,26)/2=-97,26/2
x2=-48,63
x1+x2=7,63+(-48,63)=-41
x1*x2=7,63*(-48,63)=-371,05
5)y1=√19
y2=-√19
y1+y2=√19-√19=0
y1*y2=√19*(-√19)=-√(19)^2=-19
6)x1=√(10/3)
x2=-√(10/3)
x1+x2=√(10/3)+(-√(10/3))=0
x1*x2=√(10/3)*(-√(10/3))=-10/3